Military discourse in the German-language chronicles of the XV and XVI centuries (based on the «Bernese Chronicles» by D. Schilling and V. Anshelm) - A. E. A.E. Dunaev (Вестник Самарского университета: История, педагогика, филология)
Chronicles were a popular genre of urban literature of the late Middle Ages in the German-speaking area. Being a syncretic genre, they combined the canons of chancellery writing and stylistic patterns of traditional «world» chronicles and influenced the language of not only historiographical, but also a vast layer of informative texts. Some of the (urban) chronicles represent significant linguistic and historical-cultural monuments of the respective period. Such are, in particular, the Bernese Chronicle by D. Schilling (XV century) and the work of the same name by V. Anshelm (XVI century), dedicated to the Burgundian Wars (1474–1477). We consider Schilling’s chronicle to be a representative of a mainly militaristic type of discourse, Anshelm’s chronicle to be a polydiscursive type combining informational, political and, to a lesser extent, militaristic discourses. The purpose of the article is to analyze in comparison the military vocabulary used as the most important marker of military discourse, as well as the linguistic representation and interpretation of the war protagonists in both chronicles. In the article, methods of descriptive, contextual, and cognitive-semantic analysis are used for this purpose. This study is relevant both for historical genre studies and for clarifying the parameters of military discourse in diachrony. Although military vocabulary plays a significant role in Schilling’s chronicle due to the plentitude of battle scenes, however, it has not any evaluative character, but objective in nature and is not associated with any side of the conflict. Charles the Bold is portrayed by chroniclers as an arrogant and tyrannical ruler, but Schilling describes him in darker tones than Anshelm. Anshelm’s main puppeteer is Louis XI, who skillfully manipulated the Swiss. Both chroniclers gloss over Bern’s expansionist aspirations. The difference in the interpretation of events and their participants is due to both the biography of the authors and their individual intention – legitimization by Schilling and information by Anshelm